The Effectiveness of Web-Based Computer Assisted Language Learning in Improving Arabic Speaking Skills: Efektivitas Computer Assisted Language Learning Berbasis Web dalam Menigkatkan Keterampilan Berbicara Bahasa Arab - Haniefa, Rifda; Samsudin, Mohamad (Ta'limi | Journal of Arabic Education and Arabic Studies, 2025)
Information and Communication Technology (ICT)-based learning has become an essential need to ensure that education remains relevant to the demands and changes in the world of education. The Arabic Language Education Study Program at Universitas Negeri Jakarta implements a hybrid learning model in its learning process. The implementation of the hybrid learning model requires innovations that support learning, one of which is the adoption of a web-based Computer Assisted Language Learning (CALL) approach. Researchers found that students faced challenges in mastering Arabic speaking skills, including Pronunciation, Fluency, Vocabulary, and Content and Coherence. This study employs a pre-experimental research design using a one-group pre-test and post-test method. Data were collected through oral tests, observations, and interviews. Sampling was conducted using a non-probability sampling technique, specifically purposive sampling, involving 25 first-semester students from Class A of the Arabic Language Education program. Quantitative data were analyzed using SPSS 24. The statistical test results, evidenced by the differences in the mean pre-test and post-test scores through paired sample t-test, show a sig. (2-tailed) value of 0.00 < 0.05, indicating that H0 is rejected and Ha is accepted. These results are further supported by the N-Gain score test, which shows an average N-Gain score of 71.0214, classified under Hake's category of g > 0.7 as high and Malzer's category of g > 0.7 as moderately effective. Through statistical analysis and testing, it can be concluded that learning using the web-based Computer Assisted Language Learning (CALL) approach has been proven effective in improving students' speaking skills. Keywords: Computer Assisted Language Learning (CALL), Web, Speaking Skills